LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK RESTRUKTURISASI KOGNITIF DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP NUSANTARA RAYA - Ikhsanisifa Desrianti, Hanifa; Eti Rohaeti, Euis; Agustine, Tiara (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to improve students' self-confidence at Nusantara Raya Junior High School through group guidance services with cognitive restructuring techniques. The method used in this research is mixed methods with explanatory sequential design, which combines quantitative and qualitative research. Data collection techniques for quantitative research were carried out through distributing questionnaires that had been validated by experts, while qualitative data were collected through observations and interviews with counseling teachers and three seventh grade students. This research was conducted at Nusantara Raya Junior High School with 14 seventh grade students divided into two groups: 7 students for the experimental group and 7 students for the control group. The results showed an increase in students' self-confidence through the application of group guidance services with cognitive restructuring techniques, with a sig. (2-tailed) value of 0.002 <0.05, which indicates that H1 is accepted. This means that group guidance services with cognitive restructuring techniques are effective in increasing students' self-confidence at Nusantara Raya Junior High School.